Pembuatan Laporan Keuangan Menggunakan Aplikasi Akuntansiku Pada Usaha UMKM Tahu Jeletot Pedas Nampol Di Bengkulu - Subhi, Ramdhan; Yulyanti, Oni; Rahma, Gita Rafika; Sakina, Nabilla Dwi (Universitas Dehasen Bengkulu, 2025)
Micro, Small and Medium Enterprises (MSMEs) is one of the sectors that support economic growth in Indonesia. The MSME sector is expected to be able to prepare financial reports for the businesses it runs. However, in reality, MSMEs have not been able to record bookkeeping due to a lack of understanding and resources for these problems. This community service aims to increase understanding of digital-based bookkeeping using the Akuntansiku application for MSMEs on Jalan Meranti, Bengkulu City. This service was carried out at the Nampol Spicy Tofu Jeletot MSME. One of the reasons we took the title